PENGARUH PERTUMBUHAN PERUSAHAAN, LEVERANGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Riska Dwi Amelia; Dirvi Surya Abbas; Hesty Ervianni Zulaecha; Sigit Budi Santoso (Universitas 45 Surabaya, 2022)
This research was conducted to determine the effect of company growth, leverage, profitability, and company size on company value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2021 period. The study population was 39 manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a study period of 4 years. The sample selection method is purposive sampling and there are 8 companies that match the sample criteria. The data analysis method uses panel data and ordinary least squares (OLS). The results of hypothesis testing show that partially Firm Growth has a negative and significant effect on firm value, Leverage has a negative and significant effect on firm value, Profitability has a negative and significant effect on firm value, and Company Size has a positive and significant effect on firm value. Simultaneously there is a significant influence of company growth, leverage, profitability, company size on firm value.